Discovery and structure characteristics of the intermediate-state conformation of poly(9, 9-dioctylfluorene) (PFO) in the dynamic process of conformation transformation and its effects on carrier mobility. Issue 1 (2nd January 2020) - Liu, Bin; Bai, Zeming; Li, Tao; Liu, Yang; Li, Xiaona; Zhang, Hao; Lu, Dan
Abstract : Good solution processability is a prerequisite for fabricating polymer optoelectronic devices. Abstract : Good solution processability is a prerequisite for fabricating polymer optoelectronic devices. In this research, a new PFO chain conformation called "intermediate-state conformation" was found through UV-vis absorption spectroscopy, photoluminescence spectroscopy (PL) and Raman spectroscopy in the transition process of α conformation towards β conformation. The intermediate-state conformation not only remedies the defect of film-forming caused by large aggregation of β-conformation but also gains an equivalent carrier mobility similar to that of β conformation. Simultaneously, it was found that the film with the intermediate-state conformation had a smooth surface morphology compared to the film with β-conformation, which indicates that the intermediate-state conformation has good solution processability; thus, it is more suitable for the fabrication of photoelectric films with high carrier mobility. The results of high-resolution transmission electron microscopy (HR-TEM) measurements showed that there were obvious lattice fringes in the films with the intermediate-state conformation and β conformation; this reveals that the intermediate-state conformation has a more planar conformation with extended conjugation length than the β conformation, which is very beneficial to enhance carrier mobility. The research significantly reveals the dynamic evolution of polymer structures based on conjugated polymer physics. The conclusions enrich the understanding of the structure evolution and dynamic process of conjugated polymers and present broad application prospects for photoelectric and other functional devices due to the good film-forming properties of the intermediate-state conformation.